Analysis of the Role of Professional Teacher Education in Improving the Quality of Learning in Secondary Schools - Nurjanah Nurjanah; Zuhri Zuhri; Gusma Afriani; Didik Cahyono (PT. Anagata Sembagi Education, 2025)
The Professional Teacher Education program is designed as a systematic effort to improve teacher quality by integrating educational theory, pedagogical skills and practical experience. This study analyzes the role of professional teacher education in improving the quality of learning in secondary schools. Professional teacher education is designed to equip educators with pedagogical knowledge, practical skills and a deep understanding of the subject matter, which encourages a comprehensive approach to teaching. This research uses qualitative methods, the main data of the research is obtained through literature study and document analysis from various trusted sources. These sources include scientific journals, books, government policy reports and relevant previous research. The research findings show that professional teacher education significantly contributes to improved learning outcomes by enabling teachers to adopt innovative teaching strategies, utilize modern educational technology and create inclusive learning environments. In addition, the programs also enhance teachers' ability to meet the needs of diverse students and foster critical thinking skills among students. The study concludes that continued investment in professional teacher education is critical to improving the quality of education in secondary schools and achieving long-term education goals. The implication of the implementation of Professional Teacher Education (PPG) is critical to improving the quality of education in secondary schools. The program requires curriculum development that is adaptive to the needs of the digital era, with a focus on mastering educational technology and innovative learning approaches.